Formation of Community‐Based Hypertension Practice Networks: Success, Obstacles, and Lessons Learned. Issue 6 (26th March 2014) - Dart, Richard A.; Egan, Brent M.
<x xml:space="preserve">Abstract</x> Community‐based practice networks for research and improving the quality of care are growing in size and number but have variable success rates. In this paper, the authors review recent efforts to initiate a community‐based hypertension network modeled after the successful Outpatient Quality Improvement Network (O'QUIN) project, located at the Medical University of South Carolina. Key lessons learned and new directions to be explored are highlighted.